Monolayer MoS2 quantum dots as catalysts for efficient hydrogen evolution. Issue 118 (16th November 2015) - Qiao, Wen; Yan, Shiming; Song, Xueyin; Zhang, Xing; Sun, Yuan; Chen, Xing; Zhong, Wei; Du, Youwei
Abstract : A multi-exfoliation route was used to prepare monolayer MoS2 quantum dots with improved electrocatalytic activity for hydrogen evolution. Abstract : Monolayer MoS2 quantum dots (QDs) with lateral size around 3 nm were prepared through an effective multi-exfoliation based on lithium (Li) intercalation. The effects of the number of exfoliation on the microstructures and electrocatalytic activities of hydrogen evolution reaction (HER) for MoS2 nanosheets were examined. The lateral size of the nanosheets decreases rapidly with increasing the number of exfoliation. The obtained monolayer MoS2 QDs exhibit improved HER catalytic activities with a low overpotential of approximately 120 mV and a relatively small Tafel slope of 69 mV dec −1 . Both the ultrathin structure and the abundance of exposed active edge sites make monolayer MoS2 QDs a promising HER electrocatalyst for practical application.